1992
DOI: 10.1111/j.1439-0418.1992.tb01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of the spruce bark beetle Ips typographus (L.) (Col., Scolytidae) in spruce woods1

Abstract: The dispersal of marked Ips typographus (L.) was tested by using pheromone traps placed at various distances in spruce woods in a model area in southern Bohemia, Czechoslovakia in 1989and 1990. In 1989.1 YO of the released marked beetles were captured, and 16.0 % in 1990.In both years, most of the beetles were caught within 200 m of the place of release (11.1 % in 1989 and 10.6 % in 1990) and the numbers of captured beetles decreased with increasing distance. Only 2.8 % of the released I. typographus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 9 publications
1
18
0
3
Order By: Relevance
“…During the fourth experiment, nearly 6 % of the released beetles were caught on the trap tree baited with Pheroprax®, which is comparable to recapture rates observed in other mark-recapture experiments [4,32,36] considering that only one pheromone trap tree was present in the spruce stand. Some of the marked beetles were caught shortly after their take-off, as the first catches on the trap tree occurred less than 5 [20], who observed emerging I. typographus respond to nearby pheromone traps without the need for an extended period of flight exercise.…”
Section: Beetle Dispersalsupporting
confidence: 60%
See 1 more Smart Citation
“…During the fourth experiment, nearly 6 % of the released beetles were caught on the trap tree baited with Pheroprax®, which is comparable to recapture rates observed in other mark-recapture experiments [4,32,36] considering that only one pheromone trap tree was present in the spruce stand. Some of the marked beetles were caught shortly after their take-off, as the first catches on the trap tree occurred less than 5 [20], who observed emerging I. typographus respond to nearby pheromone traps without the need for an extended period of flight exercise.…”
Section: Beetle Dispersalsupporting
confidence: 60%
“…[4,9,15,26,31] [14] on the sides carrying the collecting funnels. The proportion of trees fitted with collectors amounted to approximately 25 As it has been shown that most beetles are recaptured within the first few days of their release [15,20,25,33,36], the collecting funnels were emptied 24 h after the release, except for experiment 4 [33] for Scolytus multistriatus, Salom and McLean [26] for Trypodendron lineatum and Jactel [16] for I. sexdentatus but much lower than the minimum of 90 % take-off obtained by Botterweg [4] and Weslien and Lindelöw [32] for I. typographus.…”
Section: Introductionmentioning
confidence: 99%
“…Duelli et al, 1997;Zolubas and Byers, 1995;Zumr, 1992; for Dendroctonus frontalis e.g. Turchin and Thoeny, 1993) or passive traps (for I. typographus Franklin and Grégoire, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[e.g., Ips typographus L., Ips perturbatus (Eichoff)] suggest that almost all beetles ßy Ͻ200 m, which is substantially less than most Dendroctonus spp. (Zumr 1992, Duelli et al 1997, Werner and Holsten 1997.…”
mentioning
confidence: 98%